Dynamics Model and Its Verification of Aerospace Three-Ring Gear Reducer - Jinyong Lai; Lan Luo; Guangzhao Luo; Shiyuan Chao (Aerospace)
This paper proposes a nonlinear dynamic modeling method based on the lumped mass approach to address the challenge of modeling the vibrations of the output external gear and internal gear plate in an aerospace three-ring gear reducer. A vibration model of bending–torsion coupling with 12 degrees of freedom was established by comprehensively considering factors such as the time-varying meshing stiffness, gear transmission error, tooth side clearance, bearing support stiffness, and damping. Finite element modal analysis and vibration test results verified the vibration model’s accuracy and applicability, indicating that the model is both precise and valid. The vibration model was solved using the fourth-order, five-level Runge–Kutta method. The results show that the symmetrical arrangement design of the internal gear plate cancels the vibrations in all directions and suppresses the vibration displacement response on the output shaft.